The relationship between imagery and physical self-efficacy in athletes - Volgemute, K.; Vazne, Z.; Krauksta, D. (LASE Journal of Sport Science, 2021)
The world`s greatest athletes have very well-developed imagery skills. They use imagery every day to improve skills during training, to prepare for competitions, to adjust in technical performance and to image success, thereby strengthening their confidence and beliefs for higher achievements. Previous research has shown that the use of imagery for athletes has helped to achieve the desired goals. Physical self-efficacy has received a lot of attention in sports, and it is associated with the use of imagery. High physical self-efficiency means that athlete enjoys sports-related activities and has a constant desire for improvement and development. The aim of this study is to examine the relationship between athlete`s imagery abilities and physical self-efficacy. It was assumed that athletes who have a higher physical self-efficacy level would have higher imagery abilities than those who have lower physical self-efficacy level. The study included 69 athletes from various kinds of sports (female and male). The following research methods were used: research and analysis of literature sources, Sport Imagery Ability Questionnaire (SIAQ), Self-Efficacy to Regulate Exercise scale (SERES), mathematical statistical methods. Study findings suggest that athletes who have higher physical self-efficacy use imagery more and have better imagery abilities than athletes who have lower physical self-efficacy level.